EARLY READING READINESS LEVELS AMONG YOUNG CHILDREN IN THAILAND AND INDONESIA - Labibatul Millah; Radja Maulana Akbar; Widia Nur Jannah; Prabawati Nurhabibah; Sheilla Mae Dumaguin (Jurnal Cakrawala Pendas, 2026)
Early reading readiness in early childhood is still a concern in the world of education, because not all children have adequate literacy skills when they enter elementary school. Although comparative studies on early reading readiness between Indonesia and Thailand remain limited, this study aims to address this gap by comparing children’s reading readiness in both countries. This study aims to determine the early reading readiness of early childhood and to compare the readiness between kindergartens in Indonesia and Thailand. This research uses a qualitative descriptive method with a case study approach. Data collection techniques were carried out through observation, interviews, and documentation. The results show that there are similarities and differences in children’s reading readiness in both countries. The similarities can be seen in children’s ability to speak clearly, imitate the sounds of letters and words, recognize alphabet letters, understand the direction of reading from left to right, and show interest in books, especially picture books. In addition, children are able to hold pencils properly, write simple letters, and retell stories even though they are not yet fully complete. Meanwhile, the differences lie in the level of vocabulary mastery and the process of letter introduction. Children in Thai kindergartens tend to have a wider vocabulary and have been introduced to the alphabet since kindergarten 1, while in Indonesian kindergartens the introduction of letters is given gradually according to the child’s developmental stage. These differences are influenced by teaching methods, educational curriculum, children’s language environment, and support from teachers and parents in reading and daily communication activities. These findings contribute to a deeper understanding of early literacy development in Southeast Asia and provide implications for designing developmentally appropriate literacy programs for young children.